2004
DOI: 10.1038/431261a
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive developmental plasticity in snakes

Abstract: The morphology of organisms is generally well matched to their environment, presumably because expression of their genes is tailored either at the population or the individual level to suit local conditions: for example, snake populations that persistently encounter large prey may accumulate gene mutations that specify a large head size, or head growth may be increased in individual snakes to meet local demands (adaptive developmental plasticity). Here we test the relative contributions of genetics and environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 5 publications
2
104
0
1
Order By: Relevance
“…ongoing impact and an adaptive response to that impact or, alternatively, to developmental changes in head growth associated with dietary change subsequent to the arrival of toads. Although early studies reported that relative HS in snakes were not developmentally plastic with respect to temperature (32,33), recent studies provide evidence that relative HS in snakes can shift as a consequence of differences in mean prey size (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…ongoing impact and an adaptive response to that impact or, alternatively, to developmental changes in head growth associated with dietary change subsequent to the arrival of toads. Although early studies reported that relative HS in snakes were not developmentally plastic with respect to temperature (32,33), recent studies provide evidence that relative HS in snakes can shift as a consequence of differences in mean prey size (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of colonisation, adaptive plasticity in head growth rates may have provided an advantage to young snakes, where larger prey size stimulated a shift in relative head size as well as body size (that is, as a consequence of enhanced feeding success- Aubret et al, 2004a;Aubret and Shine, 2009). As prey size drove the evolution of snake body size at birth (Aubret, 2012), I expected a clear match between prey size available and snake body size in long isolated populations as well as mainland snake populations.…”
Section: Discussionmentioning
confidence: 99%
“…Mainland Tiger snakes typically produce litters composed of numerous small neonates that feed on a wide range of small prey items (Aubret, 2012). Insularity created a potentially huge mismatch between prey size and neonate swallowing ability (that is, due to drastically different prey assemblages), generating intense selective pressure for an increase in body and head size of neonate snakes (Forsman, 1991;King, 2002;Aubret et al, 2004a; Figure 3 Body mass rates of evolution and levels of adaptive plasticity. Rates of evolution in body mass in grams per generation were significantly correlated with the level of plasticity for head growth in response to prey size calculated for five island populations (linear regression; R 2 ¼ 0.88; F 1, 3 ¼ 21.14; Po0.019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology of organisms is generally well matched to the environment, supposedly because expression of their genes is tailored at population or at individual level to suit local conditions (Aubret et al, 2004). Teixeira-Filho et al (2001) associated the use of different microhabitats, terrestrial occupation and occupation of smooth bromeliad leaf surfaces with variations in claw curvature of lizard species inhabiting restinga habitats.…”
Section: Introductionmentioning
confidence: 99%